Pengaruh Probiotik Plus Herbal Terhadap Retensi Protein dan Retensi Lemak Benih Ikan Tawes (Barbonymus Gonionotus) - Miyalis Rimawati Sipayung; Siti Komariyah; Andika Putriningtias (Publikasi Indonesia, 2023)
This study aims to evaluate the effect of probiotics plus different herbs on commercial feed on protein retention and fat retention in tawes fish. Tawes fish is a type of aquatic fish and includes herbivorous fish that eat plants. An important factor influencing fish growth is feed, where growth occurs if the fish get the right protein. Completely Randomized Design (CRD) experimental method was used in this study, with 4 treatments and 3 replications, namely PA (Probiotic), PB (Turmeric), PC (Kingur), PD (Temulawak). Tawes fish used had a length of 5 cm, and maintenance was carried out for 40 days. The results showed that the addition of probiotics plus different herbs to commercial feeds had a significant effect on fish growth parameters such as absolute weight, absolute length growth, specific growth rate, fat retention, protein retention, survival, and feed conversion ratio. PD dosage (Temulawak) gave the best results for absolute weight gain, absolute length growth, specific growth rate, and feed conversion ratio. The highest survival rates were found in PD and PB (Turmeric), while the highest protein retention was in P4 and the highest fat retention was in PA.